Alliance between risk factors and grievousness of mucormycosis in patients suffering from COVID-19 - Shah, Esha P.; Bedi, Gautam; Bedi, Nutan; Punjabi, Sharda (International Journal of Research in Medical Sciences, 2022)
Background: Mucormycosis is a black fungal mold showing a sudden surge in covid era and left as a trail of COVID-19. It wouldn’t be wrong to say that both mucormycosis and COVID-19 prey on the immunocompromised by colonizing the nose-sinuses-orbit-eye-brain. Methods: 30 patients of suspected ROCM were included which presented a gamut of red flags ranging from numbness and pain over the cheek to diminution of vision (DOV) and diplopia. Mucormycosis was confirmed by KOH mount and gadolinium-enhanced MRI. Ophthalmic assessment included visual acuity, IOP measurement, colour vision, extraocular movements, anterior and posterior segment evaluation using slit lamp and fundoscopy. Results: Risk factors being diabetes mellitus (73.3%), history of oxygen supply during hospital stay (53.3%) and hypertension (53.3%). 16/30 (53.3%) had good vision: <6/6 but >6/12. 11/30 (36.7%) had impaired vision: <6/12 but >6/60. 3/30 (10%) had poor vision: <6/60. Finding being DOV: 14 (46.7%) >chemosis: 10(33.3%) >restricted EOM: 5 (16.7%) >periorbital cellulitis: 4 (13.3%) >congestion: 4 (13.3%) >proptosis: 4 (13.3%). Conclusions: Thus, as there is a myriad of ocular manifestations, we have tried to portray the whole spectrum here. Patients with the above-mentioned risk factors must be eyed with suspicion since delay in diagnosis and appropriate management can have calamitous implications on patient survival. However, the intervention time varies depending on the various factors like availability of the resources, awareness of the patient and expertise available for diagnosis and treatment. As this disease requires a multidisciplinary approach, ophthalmic intervention should be followed by debridement of sinuses as and when required.